Uterine macrophages as treatment targets for therapy of premature rupture of membranes by modified ADSC-EVs through a circRNA/miRNA/NF-κB pathway - Yuhua Gao; Ningning Mi; Ying Zhang; Xiangchen Li; Weijun Guan; Chunyu Bai (Journal of Nanobiotechnology, 2022)
Abstract Background Circular RNA (circRNA) is a type of stable non-coding RNA that modifies macrophage inflammation by sponging micro RNAs (miRNAs), binding to RNA-binding proteins, and undergoing translation into peptides. Activated M1 phenotype macrophages secrete matrix metalloproteinases to participate in softening of the cervix uteri to promote vaginal delivery. Methods In this study, the premature rupture of membranes (PROM) mouse model was used to analyze the role of macrophages in this process. Profiling of circRNAs was performed using a competing endogenous RNA microarray, and their functions were elucidated in vitro. Meanwhile, adipose tissue-derived stem cell-secreted extracellular vesicles (EVs) were applied as a vehicle to transport small interfering RNAs (siRNAs) targeting the circRNAs to demonstrate their biological function in vivo. Results The miRNA miR-1931 is dependent on the nuclear factor kappa-B (NF-κB) pathway but negatively regulates its activation by targeting the NF-κB signaling transducer TRAF6 to prevent polarization of M1 macrophages and inhibit matrix metalloproteinase (MMP) secretion. The host gene of circRNA B4GALNT1, also an NF-κB pathway-dependent gene, circularizes to form circRNA_0002047, which sponges miR-1931 to maintain NF-κB pathway activation and MMP secretion in vitro. In the PROM model, EVs loaded with siRNAs targeting circRNAs demonstrated that the circRNAs reduced miR-1931 expression to maintain NF-κB pathway activation and MMP secretion for accelerating PROM in vivo. Conclusions Our data provide insights into understanding PROM pathogenesis and improving PROM treatment.